1965
DOI: 10.1071/bi9650211
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Chelation and of Certain Cations on the Mobility of Foliar-Applied 45ca in Stock, Broad Bean, Peas, and Subterranean Clover

Abstract: SummaryA series of water-culture experiments was conducted with broad bean (Vicia faba L.), common stock (Mathiola incana R. Br.), subterranean clover (Trifolium Bubterraneum L.), and garden peas (PiBum Bativum L.) grown in normal-and lowcalcium nutrient solutions. Leaves of the plants were either injected or s,,!rfacetreated with an aqueous solution of 45CaCh with and without various additions to the dose. The subsequent distribution of 45Ca in the plants was determined by means of radioautographs and radioas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
13
0

Year Published

1965
1965
2004
2004

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(15 citation statements)
references
References 14 publications
2
13
0
Order By: Relevance
“…Biddulph et al (4), however, found rapid enough turnover of Ca in the cortex of beans to indicate that it too may serve as a channel for ascent of Ca. The possibility of Ca transport in the phloem also has been proposed (23,26,32,37).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Biddulph et al (4), however, found rapid enough turnover of Ca in the cortex of beans to indicate that it too may serve as a channel for ascent of Ca. The possibility of Ca transport in the phloem also has been proposed (23,26,32,37).…”
mentioning
confidence: 99%
“…The exchange is not specific. Ca ions can be freed for ascent by other divalent cations such as Sr, Mg, Mn, and Zn (1,23,24). Water and K are unable to free Ca from the exchange sites (1,24,26).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The plants were allowed to grow until they had at least seven trifoliate leaves, when the various radioactive doses as 65ZnS04 .7H20 detailed below were injected into old leaves by the method described by Millikan and Hanger (1965).…”
Section: Methodsmentioning
confidence: 99%
“…At the same time 18 of the remaining plants in both the normal-and lowcalcium series were injected via leaf 3 with 1226 p,g non-radioactive calcium (as CaCh) in 0·2 ml water, by the method described by Millikan and Hanger (1965). Twentyfour hours later, when absorption was complete, two of the injected plants from each calcium series were immediately autoradiographed and the remainder prepared for 45Ca extraction.…”
Section: (A) Redistribution Of 45ca In T Subterraneummentioning
confidence: 99%